Florida Weather and Climate : More Than Just Sunshine - Collins, Jennifer Mary; Paxton, Charles H. (Charles Hugh), 1955-; Rohli, Robert V. (Book collections on Project MUSE., 2017)
In this work, Collins, Rohli, and Paxton cover topics including geographical setting, weather fronts, the sun, thundershowers, hurricanes, tropical breezes, and tornadoes. The work also looks to the future of Florida's climate, examining the long-term implications of issues such as global warmings and natural disasters.